Learner autonomy among Malaysian adult learners through asynchronous online discussions - Ranjit Kaur Sidhu; Mohamed Amin bin Embi (Penerbit Universiti Kebangsaan Malaysia, 2009)
The use of computer-mediated communication (CMC) in course offerings in institutions of higher learning (IHLs) is seen as the catalyst towards producing autonomous lifelong learners. This paper explores Malaysian adult learners’ views of participating in asynchronous online discussions, one mode of asynchronous computer-mediated communication (ACMC), in a private university in Malaysia as a means of aiding them to become autonomous learners in the areas of planning, monitoring and decision making. The sample population comprised sixteen third-year adult course respondents (n=16) enrolled in the Listening and Speaking Course (LSC) for their Bachelor in Education (TESL) degree program. The sample comprised six (n=6) case respondents and one tutor (n=1). This descriptive case study employed a mixed method approach. Quantitative data were collected through a survey questionnaire, whereas qualitative data were obtained by analysing threaded asynchronous online interactions (AOI), conducting semi-structured interviews and analysing case respondents’ learning logs. The Þndings revealed that generally course respondents rated their abilities in planning, monitoring and decision making as average. In-depth analysis of six case respondents’ abilities also showed average abilities (overall average score = 3.3) in all three aspects of learner autonomy. This study has shown that online discussions have the potential in aiding learners in taking charge of their own learning, thus paving the way for learner autonomy. These Þndings augur well for local and global IHLs as ACMC is seen as the next e-wave of the future. However, for students to benefit from quality asynchronous online discussions, it must be accompanied by an effective follow-up system backed by dedicated educators